Work life balance policies in the Indonesian context - Afrianty, Tri Wulida (Curtin University, 2013)
The impact of Indonesian work life balance policies and family supportive supervisor behaviours (FSSB) on employee work attitudes and behaviours, including organisational citizenship behaviours (OCB), in-role performance, organisational commitment, job satisfaction and work family conflict (WFC) was investigated. Data from 30 Indonesian higher education institutions were analysed using regression analysis. Work life balance experiences in Indonesia differ from Western societies, as FSSB is more important in improving employees’ work attitudes and behaviours and resolving WFC.